The Symbolic Values of Borobudur in the Tribuana Manggala Bakti Tradition - Yatno, Tri; Ngadat, Ngadat; Putranto, Dwiyono; Siswoyo, Eko (Universitas Muhammadiyah Ponorogo, 2024)
Borobudur Temple is a cultural heritage consisting of various symbols. The Borobudur symbols contain spiritual values and moral education. Tribuana Manggala Bakti is one of a series of Vesak celebration activities in Jatimulyo Village, Kulon Progo. This activity is a Buddhist religious activity with a combination of Javanese culture. This research aims to describe the symbolic values of Borobudur in the Tribuana Manggala Bakti tradition. This research used a holistic descriptive method. The research results stated that Tribuana Manggala Bakti is a religious cultural product containing social, cultural, and spiritual values. Tribuana Manggala Bakti consists of elements of celebration, amisa puja procession, puja bakti, animal release, tree planting, and performing arts. Each of these elements is in harmony with the symbolic values of Borobudur depicted on the reliefs. Jatimulyo Buddhists strive to integrate Buddhist teachings and Javanese culture. Tribuana Manggala Bakti's cultural construction functions as a revitalization of Borobudur values, a means of strengthening Buddhist identity and strengthening interfaith unity. Tribuana Manggala Bakti is an event that transforms religious, artistic and cultural values.